Mycorrhizal Application as a Biocontrol Agent against Common Root Rot of Barley - Arabi, M. I. E.; Ayoubi, S. Kanacri Z.; Jawhar, M. (Research in Biotechnology, 2013)
This study was conducted to assess the biocontrol efficacy of vesicular arbuscular mycorrhizae (VAM) against barley common root rot caused by Cochliobolus sativus. Mycorrhization of barley was achieved by growing the plants in expanded clay mixed with 10% (v/v) VAM fungus inoculum in pots experiments. Large differences in disease reactions were observed among genotypes and among treatments. VAM treatments significantly reduced the percentage of disease severity in infected barley plants and increased significantly root biomass, which could be attributed to enhanced nutrients uptake, via an increase in the absorbing surface area. It can be concluded that the application of VAM as a biocontrol agent played an important role in plant resistance and exhibit greater potential to protect barley plants against C. sativus.